Distribution and risk assessment of phthalates in water and sediment of the Pearl River Delta - Weizhen, Zhang; Xiaowei, Zheng; Peng, Gu; Ning, Wang; Zini, Lai; Jian, He; Zheng, Zheng (Environmental science and pollution research international, 2020)
Phthalate esters (PAEs) are widely used industrial raw materials that are well known for their environmental contamination and toxicological effects as “endocrine disruptors.” In this study, environmental levels of PAEs and eco-toxicological risk assessments were determined in the eight estuaries of the Pearl River (Estuaries), main upstream tributary (Xijiang River), urban river network (River network), and nature reserve reservoir (Reservoirs). Water and sediment samples from the above water systems were collected during the low-water period (May) and the high-water period (August) between 2012 and 2014. Solid phase and ultrasonic methods were used to extract 14 different PAEs that were analyzed by gas chromatography. The analytical average recovery of PAEs in water and sediment was 75.4% ± 4.9% and 121.5% ± 8.9%, respectively. The results showed that PAEs were detected in all of the samples, and the di-n-butyl phtalate (DBP) and benzyl butyl phthalate (BBP) monomers had a detection rate of 100% in water. Similarly, in sediment samples, the detection rates of diisobutyl phthalate (D i BP), DBP, dimethoxyethyl phthalate (DMEP), BBP, di-n-octyl phthalate (D n OP), and DNP ranged from 66.7 to 100%. Among these, in sediment samples, di(2-ethylhexyl) phthalate (DEHP) and phthalic acid bis(2-butoxyethyl) ester (DBEP) had detection rates of 95.8% to 100% in the Estuaries, Xijiang River, and River network. The concentrations of Σ 14 PAEs in water samples and sediments ranged from 12.95 ± 1.97 to 6717.29 ± 112.37 ng/L and 71.99 ± 8.72 to 17,340.04 ± 227.83 ng/g-dw, respectively. During the low-water period, the average concentration of Σ 14 PAEs in water and sediment was 1159.58 ± 97.22 ng/L and 2842.50 ± 178.21 ng/g-dw, respectively, and during the high-water period, 822.83 ± 53.19 ng/L and 1936.42 ± 111.31 ng/g-dw, respectively. In water, the average concentration of Σ 14 PAEs in 2013 and 2014 was 963.39 ± 19.55 ng/L and 2815.35 ± 176.32 ng/L, respectively. In sediment, the average concentrations of Σ 14 PAEs in 2012 to 2014 were 990.10 ± 23.33 ng/g-dw, 1084.20 ± 112.12 ng/g-dw, and 1816.89 ± 79.97 ng/g-dw, respectively, with concentrations showing an increasing trend year after year (2014 > 2013 > 2012). Potential risk assessment of water ecological, the results show that exceeding environmental risk level (ERL) value in higher molecular weight plasticizer (DEHP, DMEP, DNOP, DNP) was mainly distributed in water, the lower molecular weight plasticizer (BMP, D i BP) was mainly distributed in sediment.